2010
DOI: 10.1177/030089161009600313
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl-Phosphatidylinositol-Anchored Interleukin-2 Expressed on Tumor-Derived Exosomes Induces Antitumor Immune Response in Vitro

Abstract: GPI-IL-2 gene-modified tumor cells can make the TEXs contain GPI-IL-2, resulting in increased antitumor effects. Our study provided a feasible approach for exosome-based tumor immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In immunotherapy, by ensuring the transmission of signals from CD4+ T cells to CD8+ T cells and regulating the metabolic activities of T cells, the CTL response can be optimized, which may enhance anti-cancer immunity [36]. In renal cancer, exosomes derived from glycolipidanchored-IL-12 (GPI-IL-12) gene-modified tumor cells express the tumor-associated antigen MAGE-1 and tumor rejection antigens G250 and GPI-IL-12, which significantly promote T cell proliferation and increase interferon (IFN)-γ in turn, and efficiently trigger a stronger activity of CTLs through the FasL/Fas signaling pathway [37,38]. Breast cancer exosomes inhibit both CD8+ and CD4+ T cell proliferation by initiating cell apoptosis and suppressing NK cell cytotoxicity and, hence, may inhibit the anticancer immune response [39].…”
Section: Tumor-released Exosomesmentioning
confidence: 99%
“…In immunotherapy, by ensuring the transmission of signals from CD4+ T cells to CD8+ T cells and regulating the metabolic activities of T cells, the CTL response can be optimized, which may enhance anti-cancer immunity [36]. In renal cancer, exosomes derived from glycolipidanchored-IL-12 (GPI-IL-12) gene-modified tumor cells express the tumor-associated antigen MAGE-1 and tumor rejection antigens G250 and GPI-IL-12, which significantly promote T cell proliferation and increase interferon (IFN)-γ in turn, and efficiently trigger a stronger activity of CTLs through the FasL/Fas signaling pathway [37,38]. Breast cancer exosomes inhibit both CD8+ and CD4+ T cell proliferation by initiating cell apoptosis and suppressing NK cell cytotoxicity and, hence, may inhibit the anticancer immune response [39].…”
Section: Tumor-released Exosomesmentioning
confidence: 99%
“…To perhaps better ensure membrane expression of IL2, T24 human bladder cancer cells (expressing the tumor antigen MAGE1) were transfected with a construct that linked IL2 to a glycosyl-phosphatidylinositol (GPI) anchor resulting in membrane display on the cells and apparently on the TEX as well. These GPI-IL2 TEX stimulated DCs more efficiently to generate specific CTL responses against T24 cells in vivo [ 116 ].…”
Section: Tex As Anti-cancer Vaccinesmentioning
confidence: 99%
“…Bone marrow cells from the C57BL/6 mice were cultured in RPMI-1640 medium containing 10% FCS, 10 ng/ml granulocyte macrophage-colony stimulating factor and 1 ng/ml IL-4 to generate bone marrow-derived DCs (BMDCs). Following culture growth for a period of five days, 1x10 6 /ml BMDCs were stimulated with 1 or 10 µg/ml CD40L-EXO, LacZ-EXO and Control-EXO or 1 µg/ml lipopolysaccharide (LPS) for 48 h. For FACS analysis of the BMDCs, 1x10 6 BMDCs were incubated with the corresponding PE-conjugated antibodies for 20 min.…”
Section: Generation and Fluorescence-activated Cell Sorting (Facs)mentioning
confidence: 99%
“…Exosomes may be released from various living cells, including tumor cells, dendritic cells (DCs), platelets, cytotoxic T lymphocytes (CTLs) and reticulocytes (2,5). Exosomes derived from tumor cells (TEX) contain tumor antigens, and a number of studies have indicated that exosomes may be used as an effective vaccine to initiate antitumor immunity (6,7). However, the immunogenicity of the tumor antigen in TEX is poor and the efficiency of TEX to induce antitumor immunity requires further improvement.…”
Section: Introductionmentioning
confidence: 99%